Ethno-religious Mentality in Modern Karachay-Balkar Poetry - Kerimova, Rauzat Abdullahovna; Iskhanova, Zarema Saydyevna (Journal of History Culture and Art Research, 2020)
The paper studies ethno-religious mentality issues through modern Karachay-Balkar poetry of the late XX and early XXI centuries. Global changes in the ideological, political, spiritual aspects of life have galvanized interest in determining ethnic and cultural influence on artistic creativity in modern poetry. It goes without saying that rites, customs, and other folk ethnographic elements have gradually begun disappearing; new forms are replacing them nowadays. Therefore, one of the urgent tasks in literary criticism, as we see it, is analysis of works of literature created by New-Generation Authors that reflect, in our opinion, the major trends and national peculiarities. Literary analysis of the works of new authors are carried out for the first time. We hope we could manage to trace the specifics of the interrelationship of continuity and innovation, to research evolution nature and the prospects for the development of artistic awareness of the young poets in the region.